Effects of exposure to environmental tobacco smoke on reproductive health - Lindbohm, Marja-Liisa; Sallmén, Markku; Taskinen, Helena (Scandinavian Journal of Work, Environment & Health, 2002)
The scientific evidence on the effects of preconceptional and prenatal exposure to environmental tobacco smoke on reproductive health is reviewed in this article. The evidence is the most convincing for the adverse effects of environmental tobacco smoke on birthweight. In meta-analyses, exposure to environmental tobacco smoke has been estimated to reduce mean birthweight by about 25–40 grams. The majority of the studies on low birthweight also show a moderately or slightly increased risk among infants of exposed women. There is also some support for an association between high exposure to environmental tobacco smoke and preterm birth. The evidence on the effects of environmental tobacco smoke on spontaneous abortion and birth defects is weak and inconsistent. Very little is known about the impact of exposure on fertility, menstrual function, reproductive health of men, and childhood cancer. Further studies, paying attention to study design and careful exposure assessment, are therefore needed on these associations.
Keywords: birth defect; environmental tobacco smoke; exposure; fertility; fetal growth; menstrual function; preterm birth; reproductive health; review; spontaneous abortion